An association between BPDE-like DNA adduct levels and CYP1A1 and GSTM1 polymorphisma in pterygium - Tung, Jai-Nien (Molecular Vision, 2010)
PURPOSE: Benzo[a]pyrene 7,8-diol 9,10-epoxide (BPDE), an ultimate metabolite of benzo[a]pyrene, attacks deoxyguanosine to form a BPDE-N2-dG adduct resulting in p53 mutations. Both cytochrome P4501A1 (CYP1A1) and glutathione S-transferase M1 (GSTM1) have been demonstrated to be involved in the metabolism of polycyclic aromatic hydrocarbons. The relationship between BPDE-like DNA adduct levels and CYP1A1 and GSTM1 gene polymorphisms in pterygium is not clear. Therefore, BPDE-like DNA adducts and CYP1A1 and GSTM1 polymorphisms were detected in this study to provide more molecular evidence to understand the cause of BPDE-like DNA adduct formation in pterygium. METHODS: In this study, immunohistochemical staining using a polyclonal antibody on BPDE-like DNA adducts was performed on 103 pterygial specimens. For the analysis of CYP1A1 and GSTM1 polymorphisms, DNA samples were extracted from epithelial cells and then subjected to restriction fragment length polymorphism (RFLP) and polymerase chain reaction (PCR) for the determination of mutation and genotype of CYP1A1 and GSTM1. RESULTS: BPDE-like DNA adducts were detected in 33.0% (34/103) of the pterygium samples. The differences in DNA adduct levels were associated with the genetic polymorphisms of CYP1A1 but not GSTM1. Additionally, the risk of BPDE-like DNA adduct formation for patients with CYP1A1 m1/m2 (C/T) andm2/m2 (T/T) was 9.675 fold higher than that of patients with CYP1A1 m1/m1 (C/C) types (p=0.001, 95% Confidence Interval 2.451–38.185). CONCLUSIONS: Our data provide evidence that the BPDE-like DNA adduct formation in pterygium samples was associated with CYP1A1 polymorphisms.